Concepts of physical fitness active lifestyles for wellness - Corbin, Charles B.; Welk, Greg; Corbin, William; Welk, Karen (McGraw Hill, 2013)
Provides readers with the self-management skills necessary to adopt a healthy lifestyle. This edition is thoroughly fine-tuned to ensure that the writing style, examples, and illustrations are not only contemporary, but also accessible.